Statins for Renal Patients: A Fiddler on the Roof? - Anabela Malho Guedes; Pedro Leão Neves (International Journal of Nephrology)
Atherosclerotic cardiovascular disease is the main cause of morbidity and mortality in chronic kidney disease patients. There is a raft of evidence showing that in the general population dyslipidaemia is associated with an increased risk of cardiovascular events, as well as with a greater prevalence of chronic kidney disease. Consequently, the use of statins in the general population with dyslipidaemia is not controversial. Nevertheless, the benefits of statins in patients with chronic kidney disease are more elusive. The authors review the possible effects of statins on the progression of renal disease and cardiovascular events in chronic kidney disease patients.